A care-infused market tale: on (not) maintaining relationships of trust in energy retrofit products. Issue 5 (2nd September 2020) - de Wilde, Mandy
ABSTRACT: Issues of maintenance offer exceptional opportunities for advancing our understanding of how market-driven innovation can meet societal objectives for energy transitions. In this article, I present a case study of ongoing attempts by two spin-outs and one start-up to stabilise innovative socio-technical agencements – 'customer journeys' – designed to catalyse economic exchange of certain singular goods – energy retrofit products – in the Netherlands. This market-driven innovation relies on sustaining carefully crafted relationships of trust among supply-chain actants and homeowners. I mobilise the analytical lens of 'care' to show how the multiplicity of connections that form through socio-technical agencements – and function as a market – are tentative, contested, and unpredictable. Trust relationships are in a constant process of becoming through contestation and convergence among supply-chain actants. In doing so, I expose the precarious and arduous work involved in maintaining a market for singular public goods. This implies a knowledge politics as well: in a call to sensitise us, market scholars, to processes of maintenance integral to market-driven innovation for energy transitions I propose to advance Callon's call to civilise markets by sharing troubled, though encouraging, care-infused market tales in an effort to counteract the storification of energy transitions as innovation fairy tales.